2022
DOI: 10.1177/09612033221081691
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and disease related comorbidities in systemic lupus erythematosus: Data from an Egyptian cohort

Abstract: Background Systemic lupus erythematosus (SLE) is a complex autoimmune disorder with significant disease-related comorbidity and considerably high mortality. Aim of the work Explore the survival rates and the spectrum of disease related comorbidities in an Egyptian cohort afflicted by SLE. Methods This is a single center observational cohort study performed in one of the leading medical Schools governmental hospitals for teaching and training in the North African region and Middle East sectors Kasr Alainy Schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…In the cohort as a whole, 15 deaths were recorded after 6 months of follow-up, representing a death rate of 17.0%. This frequency is higher than those found in Europe [17], North Africa [18] and United States [19]. In sub-Saharan Africa, Teclessou et al [20] and Daboiko et al [21] reported death rates of 22.5% and 22.4% respectively.…”
Section: Discussionmentioning
confidence: 77%
“…In the cohort as a whole, 15 deaths were recorded after 6 months of follow-up, representing a death rate of 17.0%. This frequency is higher than those found in Europe [17], North Africa [18] and United States [19]. In sub-Saharan Africa, Teclessou et al [20] and Daboiko et al [21] reported death rates of 22.5% and 22.4% respectively.…”
Section: Discussionmentioning
confidence: 77%
“…1,3,6 The 10-year survival rate in the present study falls within the range of recent investigations (68.8%-94.9%). 4,5,[19][20][21][22] Due to the development of novel pharmaceutical agents, the trend in mortality rates decreased in recent years as compared to that few decades ago. 1,3,23,24 Ethnic, geographic, and secular changes and social-economic differences contribute to the heterogeneity of survival rates in SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Although the treatment of SLE has progressed in recent decades, its relative risk of mortality is high. [3][4][5][6] The attempt to improve survival in SLE patients cannot neglect the management of risk factors of mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Another multi-center retrospective cohort study reported that the cumulative 5-year survival rate was 96% among Korean SLE patients [ 83 ]. A cohort of SLE patients in a single center in China showed a 5-year survival rate of 93.8% [ 92 ], and an Egyptian study reported that the overall cumulative survival rate was 82.9% at 5 years after SLE diagnosis [ 93 ], which were lower than that in Korea. Further information on mortality and causes for 20, 30, and 40 years would be helpful to ensure a higher quality of life in patients.…”
Section: Main Subjectsmentioning
confidence: 99%